A Survey of WSN Testbeds Deployment - Godoy, Pablo Daniel (2012)
A WSN testbed is a WSN (wireless sensor network) deployed in a controlled environment, that users can use for testing new developments, such as communication protocols, applications, etc. Users can access remotely, configure or program nodes, retrieve experimental results, and in some cases, interact in realtime with the WSN nodes. This paper is a survey about different approaches used for building WSN testbeds. This information can be useful for building new WSN testbeds, or for developing improvements and solutions to current problems of WSN testbeds. The paper presents information about: architecture, hardware and software components, interaction with users, open issues and possible improvements.